SOCIOLOGICAL INTERPRETATION OF SOCIAL-PROFESSIONAL MOBILITY - Ekaterina A. Pobozhenskaya (Вестник Северо-Кавказского федерального университета, 2022)
The point of this article is analysis of the definition social-professional mobility. The author offers a sociological argumentation for the differentiation of the terms mobility, social mobility, social-professional mobility.